Retraction Notice: Mapping Generative Artificial Intelligence (GAI’s) Exciting Future: From Gemini to Q* and Beyond - Ahktar, Zarif Bin (EAI Endorsed Transactions on AI and Robotics, 2024)
The article Mapping Generative Artificial Intelligence (GAI’s Exciting Future: From Gemini to Q* and Beyond has been retracted at the request of EAI’s Research Integrity Committee. The paper is being removed on the grounds plagiarism and misrepresentation of academic affiliation.